Implementation of Face-to-Face Classes Amidst Pandemic: A Phenomenological Study - David, Jemima C.; Urbano, Roselle D. Urbano (International Journal of Education, Teaching, and Social Sciences, 2024)
This study delved into the lived experiences of teachers, parents, and students during the COVID-19 pandemic, examining how it contributed to stress and burnout. Using a phenomenological approach, the research aimed to grasp the meaning of these experiences by exploring the lives of those affected. Employing qualitative research such as participant observations, in-depth interviews, and focus groups, thirteen distinct themes emerged. These themes encompassed financial, parental, and teacher support and environmental and affective variables for students. Instructors' themes included technological expertise, student engagement, family support, and environmental factors, while parents' themes covered financial, instructional, technological, and personal factors. Notably, self-determination, autonomous learning, interactive digital tools, and innovative teaching methods emerged as pivotal aspects influencing student learning in the online environment